Evaluación de la viabilidad técnico-financiera de las operaciones de Workover mediante simulación numérica para la reapertura del campo Hato nuevo (2017)
This project has the objective to achieve the reopening of the Hato Nuevo Oil Field, located in the Upper Magdalena Valley Basin, which is closed due to the high production of water in the Caballos producing formation. Through Workover operations, the exploitation of the Villeta generating rock, which has not been previously exploited, for this reason, with the help of the petrophysical parameters, pressure data and parameters of the Tenay Analogue Field, an initial production rate was determined, for three probabilistic production scenarios.